Resin-metal composite body and method of manufacturing resin-metal composite body

The resin-metal composite with controlled surface roughness and specific plating methods addresses the issue of peeling by enhancing adhesion and strength, suitable for industrial applications.

JP2025007236APending Publication Date: 2025-01-17RICOH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023108505
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Metal plating on resin base materials peels off due to impact, particularly in industrial water turbines, leading to poor adhesion and reduced strength.

Method used

A resin-metal composite with a resin base material having a surface roughness Sq of 1.5 μm or more and Sku of 4.5 μm or less, combined with metal plating, utilizing a manufacturing method that includes electroless and electrolytic plating processes without surface treatment.

Benefits of technology

Enhances adhesion between the resin base material and metal plating, improving the strength and durability of the composite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007236000014
    Figure 2025007236000014
  • Figure 2025007236000001
    Figure 2025007236000001
  • Figure 2025007236000002
    Figure 2025007236000002
Patent Text Reader

Abstract

To provide a resin-metal composite body in which the adhesion between a resin base material and a metal plating is excellent and by which it is possible to improve the strength of the resin base material.SOLUTION: A resin-metal composite body includes a resin base material having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less, and a metal plating on the resin base material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin-metal composite and a method for producing a resin-metal composite. [Background technology]

[0002] 2. Description of the Related Art Conventionally, there has been known a technique for decorating a surface of a base material made of resin (hereinafter, sometimes referred to as a "resin base material") by plating it with a metal (see, for example, Patent Document 1). Summary of the Invention [Problem to be solved by the invention]

[0003] However, metal plating of resin substrates for decorative purposes does not anticipate exposure to strong impacts. In particular, even when metal plating of resin substrates for decorative purposes is performed on components used in industrial water turbines, there is a problem that the metal plating can peel off due to impacts from water currents, etc. In view of the above problems, an object of the present invention is to provide a resin-metal composite that has excellent adhesion between a resin substrate and a metal plating and can improve the strength of the resin substrate. [Means for solving the problem]

[0004] The resin-metal composite of the present invention, as a means for solving the above problems, is characterized by having a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less, and a metal plating on the resin substrate. Effect of the Invention

[0005] According to the present invention, it is possible to provide a resin-metal composite that has excellent adhesion between a resin substrate and a metal plating and can improve the strength of the resin substrate. [Brief description of the drawings]

[0006] [Figure 1]FIG. 1 is a schematic cross-sectional view showing a resin-metal composite according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] (resin metal composite) Fig. 1 is a schematic cross-sectional view showing a resin metal composite according to one embodiment of the present invention. The resin metal composite 100 shown in Fig. 1 has a resin substrate 10 and a metal plating 20 on the resin substrate.

[0008] <Resin substrate> The resin substrate has a substrate surface (i.e., the interface between the resin substrate 10 and the metal plating 20) with a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less. The resin substrate preferably has a surface roughness Sq of 1.5 μm or more and 20 μm or less and a surface roughness Sku of 1.0 μm or more and 4.5 μm or less. When the surface roughness Sq is 1.5 μm or more and the surface roughness Sku is 4.5 μm or less, the adhesion between the resin substrate and the metal plating is excellent.

[0009] The surface roughness Sq corresponds to the standard deviation of height within a defined area, and is defined by the following formula (1). [ka] (In the above formula (1), A represents the area of ​​the defined region, x represents the x-axis coordinate, y represents the y-axis coordinate, and z represents the z-axis coordinate.)

[0010] The surface roughness Sku indicates the sharpness of the height distribution in a defined area, and is defined by the following formula (2). [ka] (In the above formula (2), A represents the area of ​​the defined region, x represents the x-axis coordinate, y represents the y-axis coordinate, and z represents the z-axis coordinate.)

[0011] The method for measuring the surface roughness Sq and the surface roughness Sku is not particularly limited and can be appropriately selected depending on the purpose. For example, an image of the resin substrate surface can be obtained at a magnification of 1500 times by Opt-SEM measurement in high image quality depth synthesis mode using an electron microscope (VHX7000 manufactured by Keyence Corporation), and the surface roughness of the entire area of ​​the obtained image can be calculated using analysis software of the same device.

[0012] The resin substrate is preferably not subjected to an acid treatment or a blast treatment, but may be subjected to a surface treatment as required.

[0013] The resin substrate contains a resin and a filler, and may further contain other components as necessary.

[0014] -resin- The resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the resin include thermoplastic resins, thermosetting resins, photocurable resins, recycled plastics, bioplastics, and the like.

[0015] The aforementioned recycled plastic is plastic made by reusing plastic that has been discarded after one use. It is the oldest among environmentally friendly plastics, and many products are already made from recycled plastic. The two main technologies for producing recycled plastics are "material recycling" and "chemical recycling."

[0016] Material recycling is a technology that uses used plastic as raw material to create new products. For example, used PET bottles are collected and sorted, then crushed, washed, and subjected to processes such as removing foreign matter to become recycled plastic called flakes or pellets. This recycled plastic is then used to make other plastic products such as trays or films, or converted into fibers to make clothing. However, recycled plastic made through material recycling tends to be of lower quality than new plastic, and has the disadvantage that its uses are limited.

[0017] Chemical recycling is a technology that chemically breaks down used plastics, returning them to petroleum-based materials and monomers, and turns them into plastic materials equivalent to new materials. It is a newer technology than material recycling, and has the excellent feature of being able to recycle even if different types of plastics are mixed together or if there is foreign matter or dirt. With the development of chemical recycling technology, it is now possible to realize "bottle to bottle" recycling, where plastic bottles are made from used plastic bottles.

[0018] The recycled plastic is not particularly limited and can be appropriately selected depending on the purpose. Examples of the recycled plastic include polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, polybutadiene, acrylonitrile-butadiene-styrene copolymer (ABS), polystyrene (PS), acrylonitrile-chlorinated polyethylene-styrene copolymer resin (ACS), acrylonitrile-styrene copolymer resin (AS), polybutene resin, alkyd resin, amino resin, acrylonitrile-acrylic rubber-styrene copolymer resin (ASA), bismaleimide triazine resin, chlorinated polyether, chlorinated polyethylene, allyl resin, epoxy resin, ethylene-α-olefin copolymer, ethylene-vinyl acetate-vinyl chloride copolymer, ethylene-vinyl chloride copolymer, ethylene vinyl alcohol resin (EVA), ionomer, methacrylic-styrene copolymer, nitrile resin, polyester [polyethylene terephthalate (PE T), polybutylene terephthalate (PBT), etc.), olefin vinyl alcohol copolymer, petroleum resin, phenol resin, polyacetal, polyacrylate, polyamide, polyarylsulfone, polybenzimidazole, polybutylene, polycarbonate, polyether ether ketone, polyether ketone, polyether nitrile, polyether sulfone, polyketone, methacrylic resin, polymethylpentene, polyphenylene ether, polyphenylene sulfide, polysulfone, butadiene-styrene resin, polyurethane, polyvinyl acetal, polyvinyl alcohol, polyvinyl chloride, polyvinylidene chloride, silicone resin, polyvinyl acetate, xylene resin, crosslinked polyolefin such as crosslinked polyethylene, crosslinked polystyrene, unsaturated polyester resin, urea resin, melamine resin, fluororesin, biodegradable resin, thermoplastic elastomer, ethylene-propylene-diene copolymer (EPDM), etc.

[0019] The bioplastics are a general term for plastics made from biomass (biomass plastics) and biodegradable plastics (biodegradable plastics). However, just because something is derived from biomass does not necessarily mean it is biodegradable, and conversely, just because something is biodegradable does not necessarily mean that the raw material is biomass.

[0020] The biomass plastic is a plastic made from biological resources (biomass), which are renewable resources. There are two main methods of synthesis. The first type is a polymer made by using starch or sugar derived from corn or sugarcane as a raw material, converting them into different substances by fermentation or the like, synthesizing monomers, and then polymerizing them. Examples include polylactic acid (PLA), which is a polymer of lactic acid, and polyhydroxyalkanoate (PHA), which is produced by microorganisms. The second type is made by extracting polysaccharides such as cellulose from plants, etc., and derivatizing them while utilizing the structure of the polymer skeleton to give them thermoplasticity (cellulose acetate, etc.). Polymers made from biomass had been widely studied (mainly cellulose derivatives such as nitrocellulose) even before polymers derived from fossil resources were synthesized. However, from the first half of the 20th century, high-performance polymers derived from fossil resources became available for cheap mass production (nylon, polypropylene, etc.), and research on biomass waned. From the second half of the 20th century, due to growing social awareness of the environment, materials made from biomass have once again attracted attention.

[0021] The biodegradable plastic means a plastic that can be used in the same way as normal plastic, and after use, is ultimately decomposed into water and carbon dioxide by the action of microorganisms present in nature. There are two types of biodegradable plastics: those derived from biological resources (biomass) (biomass plastics) and those derived from petroleum (petroleum synthetic plastics). As long as they are biodegradable, it doesn't matter what the raw material is. The mainstream is biomass plastics, which are made from biological resources (biomass), and many of them are made from starch or sugar. However, not all plastics made from biomass are biodegradable. For example, bio-PET and bio-PE are made from biomass, but are not biodegradable. The main biodegradable plastics made from biomass include polylactic acid, polycaprolactone, polyhydroxyalkanoate (PHA, microbial polyester), polyglycolic acid, modified polyvinyl alcohol, casein, modified starch, low-substituted polysaccharide derivatives (low-substituted cellulose acetate, etc.), etc. Petroleum-derived plastics include PET copolymers.

[0022] -Filler- The filler can be appropriately selected depending on the desired physical properties to be improved, but is preferably a fibrous filler such as cellulose nanofiber, glass fiber, bismaleimide resin, etc. By using a fibrous filler such as cellulose nanofiber, glass fiber, bismaleimide resin, etc. as the filler, it is possible to achieve a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less without performing a surface treatment on the resin substrate.

[0023] As the filler, commercially available products can be used, such as Cellenpia (manufactured by Nippon Paper Industries Co., Ltd.), Senaf (manufactured by Hattori Shoten Co., Ltd.), SS05-413 (manufactured by Nitto Boseki Co., Ltd.), BMI-TMH (manufactured by Yamato Chemical Industry Co., Ltd.), SC-5500 (manufactured by Admatechs Co., Ltd.), and PBT (manufactured by Ricoh Co., Ltd.).

[0024] -Other ingredients- The other components are not particularly limited and can be appropriately selected depending on the purpose. For example, a pigment dispersion can be used.

[0025] There are no particular limitations on the shape, size, etc. of the resin substrate 10, and they can be appropriately selected depending on the purpose. Since the metal plating 20 is formed on the surface of the resin substrate 10, the shape and size of the resin substrate 10 are approximately the same as those of the resin-metal composite 100, and therefore the shape and size of the metal-resin composite 100 can be determined depending on the intended use, etc.

[0026] The method for forming the resin substrate 10 is not particularly limited and can be appropriately selected depending on the purpose. For example, the resin substrate 10 can be formed by mold molding, cutting, or the like, using an ultraviolet-curable composition with a 3D printer.

[0027] The 3D printer is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include fused deposition modeling (FDM), stereolithography, material jetting, binder jetting, powder lamination, powder bonding (adhesion), etc. By using a three-dimensional printer to form parts having a shape corresponding to the shape of the power generation unit, it is possible to quickly respond to assembly, maintenance, inspection, replacement of damaged parts, etc. of the hydroelectric power generation device.

[0028] -Ultraviolet curable composition- The ultraviolet ray curable composition (hereinafter, sometimes referred to as "ink") is not particularly limited and can be appropriately selected depending on the purpose. For example, it can contain a monomer, an oligomer, a filler, a crosslinking agent, a pigment dispersion, a polymerization initiator, etc.

[0029] The monomer is not particularly limited and can be appropriately selected depending on the purpose, and commercially available products can be used. Examples of commercially available products include DCP (tricyclodecane dimethanol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.), HEA (hydroxyethyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), Viscoat #200 (cyclic trimethylolpropane formal acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, iso Butyl (meth)acrylate, t-butyl (meth)acrylate, isooctyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydixylethyl (meth)acrylate acrylate, ethyl diglycol (meth)acrylate, cyclic trimethylolpropane formal mono (meth)acrylate, phenoxyethyl (meth)acrylate, (meth)acrylic acid 2-(2-vinyloxyethoxy)ethyl, tetrahydrofurfuryl (meth)acrylate, imide (meth)acrylate, isoamyl (meth)acrylate, ethoxylated succinic acid (meth)acrylate, trifluoroethyl (meth)acrylate, ω-carboxypolycaprolactone mono (meth)acrylate, N-vinylformamide, cyclohexane Cyclohexyl (meth)acrylate, benzyl (meth)acrylate, methylphenoxyethyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, tribromophenyl (meth)acrylate, ethoxylated tribromophenyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, (meth)acryloylmorpholine, phenoxydiethylene glycol (meth)acrylate, vinyl caprolactam, vinyl pyrrolidone,2-Hydroxy-3-phenoxypropyl (meth)acrylate, 1,4-cyclohexanedimethanol mono (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, stearyl (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, lauryl (meth)acrylate, isodecyl (meth)acrylate, 3,3,5-trimethylcyclohexanol (meth)acrylate, isooctyl (meth)acrylate, octyl / decyl (meth)acrylate, tridecyl (meth)acrylate acrylate, caprolactone (meth)acrylate, ethoxylated (4) nonylphenol (meth)acrylate, methoxypolyethylene glycol (350) mono(meth)acrylate, methoxypolyethylene glycol (550) mono(meth)acrylate, hexadiol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol tri(meth)acrylate acrylate, neopentyl glycol di(meth)acrylate, bispentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethoxylated 1,6-hexanediol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tetraethylene glycol di(meth)acrylate acrylate, 2-n-butyl-2-ethyl 1,3-propanediol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, hydroxypivalic acid trimethylolpropane tri(meth)acrylate, ethoxylated phosphoric acid tri(meth)acrylate, ethoxylated tripropylene glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate,Stearic acid modified pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, tetramethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, propoxylated glyceryl tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate acrylate, dipentaerythritol hydroxypenta(meth)acrylate, neopentyl glycol oligo(meth)acrylate, 1,4-butanediol oligo(meth)acrylate, hydroxypivalic acid neopentyl glycol (meth)acrylic acid adduct, 1,6-hexanediol oligo(meth)acrylate, trimethylolpropane oligo(meth)acrylate, pentaerythritol oligo(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, etc. These may be used alone or in combination of two or more.

[0030] The content of the monomer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50% by mass or more and less than 70% by mass based on the total amount of the ultraviolet-curable composition.

[0031] The oligomer is not particularly limited and can be appropriately selected depending on the purpose, and commercially available products can be used. Examples of commercially available products include UV-2000B, UV-2750B, UV-3000B, UV-3010B, UV-3200B, UV-3300B, UV-3700B, UV-6640B, UV-8630B, UV-7000B, UV-7610B, UV-1700B, UV-7630B, UV-6300B, UV-6640B, UV-7550B, UV-7600B, UV-7605B, UV-7610B, UV-7630B, UV-7640B, UV-7650B, and UT manufactured by Nippon Chemical Synthetic Co., Ltd. -5449, UT-5454; Sartomer's CN104, CN902, CN902J75, CN929, CN940, CN944, CN944B85, CN959, CN961E75, CN961H81, CN962, CN963, CN963A80, CN963B80, CN963E75, CN963E80, CN963J85, CN964, CN965, CN965A80, CN966, CN966A80, CN966B85, CN966H90, CN966J75, CN968, CN969 , CN970, CN970A60, CN970E60, CN971, CN971A80, CN971J75, CN972, CN973, CN973A80, CN973H85, CN973J75, CN975, CN977, CN977C70, CN9 78, CN980, CN981, CN981A75, CN981B88, CN982, CN982A75, CN982B88, CN982E75, CN983, CN984, CN985, CN985B88, CN986, CN989, CN991, C N992, CN994, CN996, CN997, CN999, CN9001, CN9002, CN9004, CN9005, CN9006, CN9007, CN9008, CN9009, CN9010, CN9011, CN9013, CN9018 , CN9019, CN9024, CN9025, CN9026, CN9028, CN9029, CN9030, CN9060, CN9165, CN9167, CN9178, CN9290, CN9782, CN9783, CN9788, CN9893;Examples of such compounds include EBECRYL210, EBECRYL220, EBECRYL230, EBECRYL270, KRM8200, EBECRYL5129, EBECRYL8210, EBECRYL8301, EBECRYL8804, EBECRYL8807, EBECRYL9260, KRM7735, KRM8296, KRM8452, EBECRYL4858, EBECRYL8402, EBECRYL9270, EBECRYL8311, EBECRYL8701, and EBECRYL8606 manufactured by Daicel-Cytec Co., Ltd.; These may be used alone or in combination of two or more. It is also possible to use synthetic oligomers instead of commercially available products, or to use these in combination.

[0032] The content of the oligomer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10% by mass or more and 50% by mass or less based on the total amount of the ultraviolet ray curable composition.

[0033] The filler is not particularly limited and can be appropriately selected depending on the purpose, and the same fillers as those described above can be used.

[0034] The content of the filler is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 0.1% by mass to 10% by mass, and more preferably from 0.5% by mass to 5% by mass, based on the total amount of the ultraviolet-curable composition.

[0035] The crosslinking agent is not particularly limited and can be appropriately selected depending on the purpose, and commercially available products can be used. Examples of commercially available products include KBM-503 (manufactured by Shin-Etsu Silicone Co., Ltd.) and KBM-603 (manufactured by Shin-Etsu Silicone Co., Ltd.).

[0036] The polymerization initiator is not particularly limited as long as it is capable of generating active species such as radicals and cations by the energy of active energy rays and initiating polymerization of a polymerizable compound (monomer or oligomer), and can be appropriately selected depending on the purpose. Examples of the radical polymerization initiator include aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, thiophenyl group-containing compounds, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having a carbon-halogen bond, and alkylamine compounds. Commercially available products can be used for these, and examples include TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, manufactured by BASF), acetophenone, 2,2-diethoxyacetophenone, p-dimethylaminoacetophenone, benzophenone, 2-chlorobenzophenone, p,p'-chlorobenzophenone, p,p-bisdiethylaminobenzophenone, Michler's ketone, benzyl, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether ... Benzoin-n-propyl ether, benzoin isobutyl ether, benzoin-n-butyl ether, benzyl methyl ketal, thioxanthone, 2-chlorothioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-one, 1-(4-isopropylphenyl)2-hydroxy-2-methylpropan-1-one, methyl benzoyl formate, 1-hydroxycyclohexyl phenyl ketone, azobisisobutyronitrile, benzoyl peroxide, di-tert-butyl peroxide, and the like.

[0037] The pigment in the pigment dispersion is not particularly limited and can be appropriately selected depending on the purpose, and commercially available products can be used, such as Carbon Black #10 (manufactured by Mitsubishi Chemical Corporation).

[0038] <Other ingredients> The ultraviolet ray curable composition may contain other components as necessary. The other components are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include polymerization inhibitors, colorants, organic solvents, surfactants, leveling agents, defoamers, fluorescent brightening agents, penetration promoters, wetting agents (moisturizing agents), fixing agents, viscosity stabilizers, antifungal agents, preservatives, antioxidants, ultraviolet absorbers, chelating agents, pH adjusters, and thickeners.

[0039] <Metal plating> The metal plating is provided on the resin substrate, and by reinforcing the resin substrate, the strength of the resulting metal-resin composite can be improved compared to a case where only the resin substrate is used.

[0040] The metal plating is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include nickel plating, copper plating, chrome plating, etc. The metal plating may be a plating made of a single metal, or may have a structure in which multiple platings made of different metals are laminated. The metal plating preferably includes at least any one of nickel plating, copper plating, and chrome plating.

[0041] The thickness of the metal plating (meaning the total thickness of the layers when the metal plating has a structure in which multiple layers are laminated) can be appropriately selected depending on the purpose, but from the viewpoint of the strength of the metal-resin composite, it is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 50 μm or more. In addition, from the viewpoint of adhesion between the resin substrate and the metal plating, the thickness of the metal plating is preferably 1,000 μm or less, more preferably 500 μm or less, and even more preferably 300 μm or less. Therefore, a suitable range of the thickness of the metal plating may be a range arbitrarily selected and combined from the lower limit and upper limit of the thickness, for example, 10 μm or more and 1,000 μm or less, 20 μm or more and 500 μm or less, or 50 μm or more and 300 μm or less. The thickness of the metal plating can be measured, for example, by using a digital micrometer to measure the thickness of the resin substrate before metal plating and the thickness of the resin-metal composite after metal plating, and calculating the difference by subtracting the thickness of the resin substrate before metal plating from the thickness of the resin-metal composite after metal plating.

[0042] The metal plating having a structure in which multiple layers are laminated is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable to use a metal material with ductility as the base layer and a metal material with rigidity as the upper layer. For example, by forming layers in the order of copper plating with ductility and nickel plating with rigidity, it is possible to improve both adhesion and mechanical properties during stress deformation. In this case, the thickness of the extensible metal plating layer is preferably at least 1 time, more preferably at least 1.5 times, the thickness of the rigid metal plating layer, and particularly preferably 2 to 5 times, from the viewpoint of compatibility between the extensible metal plating layer and the rigid metal plating layer in terms of conformability.

[0043] (Method of manufacturing resin-metal composite) The present invention includes a method for producing the metal-resin composite, which comprises plating a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less. The method for producing the resin-metal composite preferably does not include a step of surface-treating the resin substrate by acid treatment, blast treatment, or the like.

[0044] The plating process can be performed by a method known in the art according to the metal used for plating. For example, electroless plating can be used for nickel plating, and electrolytic plating can be used for copper plating. In addition, when a metal plating having a structure in which multiple layers are laminated is used, a combination of multiple plating methods can be used to perform metal plating in which multiple layers are laminated. In addition, when using an electrolytic plating method, since electrolytic plating cannot be performed directly on a resin substrate, it is necessary to form a conductive layer (underlayer). Therefore, in one embodiment, the plating process has an underlayer formation step in which electroless plating is performed, and an electrolytic plating layer formation step in which electrolytic plating is subsequently performed. For example, nickel plating is formed as an underlayer by first electroless plating, and copper plating is formed by subsequent electrolytic plating. In the electrolytic plating layer formation step, multiple electrolytic platings using different metals may be performed, for example, electrolytic copper plating may be followed by electrolytic nickel plating. In a preferred embodiment, in order to apply a rigid nickel plating on an extensible copper plating, it is preferable to have a step of performing electroless plating (forming a base layer), a step of performing electrolytic copper plating (forming a copper plating), and a step of performing electroless or electrolytic nickel plating (forming a nickel plating). In addition, instead of or after forming the nickel plating, a step of performing electroless chromium plating may be included.

[0045] The underlayer forming step in which electroless plating is performed typically includes electroless nickel plating, which can be performed, for example, by the following method. First, the resin substrate is immersed in a 200 mL container containing a 2 mol NaOH aqueous solution and ultrasonically cleaned for 15 minutes, and then washed with pure water. Thereafter, the substrate is dried in a thermostatic bath at 60°C for 20 minutes, and then immersed in Nickel Boomer CON1 liquid (manufactured by Nippon Kagaku Sangyo Co., Ltd.), stirred with a stirrer at 24°C for 10 minutes, and then washed with pure water. Thereafter, the substrate is immersed in Nickel Boomer 46 solution (manufactured by Nippon Chemical Industries Co., Ltd.), stirred with a stirrer at 60° C. for 1 minute, and then washed with pure water. Thereafter, the sample is immersed in Nickel Boomer 8509B-B solution (manufactured by Nippon Chemical Industries Co., Ltd.), stirred with a stirrer at 60°C for 30 seconds, and then washed with pure water. Thereafter, the process from immersion in the nickel boomer 46 liquid is repeated twice. The electroless nickel plating solution is stirred with a stirrer at 60°C, washed with pure water, and dried in a thermostatic bath at 60°C for 20 minutes.

[0046] The electrolytic plating step typically includes electrolytic copper plating and electrolytic nickel plating. For example, electrolytic plating can be performed by the following method. First, the resin substrate that had been electrolessly plated in the undercoat layer formation process was immersed in an electrolytic copper plating bath and was charged at 24°C with a current density of 4.5 A / dm using a DC stabilized power supply IPS-3610D (manufactured by ISO-TECH). 2 The mixture is then subjected to electrolytic copper plating and washed with pure water. After electrolytic copper plating, the resin substrate was immersed in an electrolytic nickel plating bath and the plating was performed at 55°C with a current density of 5A / dm using a DC stabilized power supply IPS-3610D (manufactured by ISO-TECH). 2 The nickel plating is then performed and the mixture is washed with pure water.

[0047] In one embodiment, the method further includes a step of forming an electroless plating film following the electrolytic plating film forming step. Typical examples include electroless nickel plating and electroless chromium plating. For example, the electroless plating can be performed by the following method. First, the resin substrate that has been electrolytically plated in the second step is immersed in a 200 mL container containing a 2 mol NaOH aqueous solution, ultrasonically cleaned for 15 minutes, and then washed with pure water. Thereafter, the substrate is dried in a thermostatic bath at 60°C for 20 minutes, and then immersed in Nickel Boomer CON1 liquid (manufactured by Nippon Kagaku Sangyo Co., Ltd.), stirred with a stirrer at 24°C for 10 minutes, and then washed with pure water. Thereafter, the substrate is immersed in Nickel Boomer 46 solution (manufactured by Nippon Chemical Industries Co., Ltd.), stirred with a stirrer at 60° C. for 1 minute, and then washed with pure water. Thereafter, the sample is immersed in Nickel Boomer 8509B-B solution (manufactured by Nippon Chemical Industries Co., Ltd.), stirred with a stirrer at 60°C for 30 seconds, and then washed with pure water. Thereafter, the process from immersion in the nickel boomer 46 liquid is repeated twice. Thereafter, the electroless nickel plating solution is stirred with a stirrer at 60° C., and then the substrate is washed with pure water and dried in a thermostatic bath at 60° C. for 20 minutes.

[0048] In the electroless plating forming step, it is preferable to perform electroless nickel plating using an electroless nickel solution containing a phosphorus-nickel compound with a phosphorus content of 5% or more, thereby improving acid resistance, abrasion resistance, ductility, etc. EXAMPLES

[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way. In the following examples, "parts" means "parts by mass" and "%" means "% by mass".

[0050] <Ink Preparation> Based on the materials and contents (parts by mass) shown in Table 1 below, ultraviolet-curable compositions 1 to 23 (hereinafter sometimes referred to as "inks 1 to 23") were prepared by a conventional method.

[0051] [Table 1]

[0052] The product names and manufacturing company names of the ink materials listed in Table 1 are as follows:

[0053] [monomer] DCP: Tricyclodecane dimethanol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) ·HEA: Hydroxyethyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) Viscoat #200: Cyclic trimethylolpropane formal acrylate (Osaka Organic Chemical Industry Co., Ltd.)

[0054] [Oligomer] ·CN104 (Sartomer) EBECRYL8606 (manufactured by Daicel)

[0055] [Filler] · Cellenpia (manufactured by Nippon Paper Industries Co., Ltd.) Senaf (manufactured by Hattori Shoten Co., Ltd.) SS05-413 (manufactured by Nittobo Co., Ltd.) ·BMI-TMH (manufactured by Daiwa Chemical Industry Co., Ltd.) ·SC-5500 (Admatechs) ·PBT (manufactured by Ricoh Co., Ltd.) AHP-200 (manufactured by Nippon Light Metal Co., Ltd.)

[0056] [Crosslinking agent] ·KBM-503 (Shin-Etsu Silicone Co., Ltd.) ·KBM-603 (Shin-Etsu Silicone Co., Ltd.)

[0057] [Polymerization initiator] TPO: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (BASF)

[0058] [Pigment] A pigment made by mixing carbon black #10 (manufactured by Mitsubishi Chemical Corporation) with polymer dispersant S32000 (manufactured by Lubrizol Japan) in a mass ratio of 3:1.

[0059] (Examples 1 to 10 and Comparative Examples 1 to 5) <Preparation of Resin Substrate> The inks shown in Tables 2 and 3 below were used to fill a 3D printer (MARS3Pro, manufactured by ELEGOO) and a 4.0 x 1.0 x 80.0 mm model was created under conditions of a resolution of 4098 x 2560, a layer height of 0.05 mm, the number of initial layers being 5, an exposure time for the initial layer being 35 seconds, and an exposure time of 2.5 seconds. A secondary curing was then performed using a secondary curing device (Form Cure, manufactured by Formlabs) at 60°C for 90 minutes to form a resin substrate.

[0060] <Surface treatment> The surface of the formed resin substrate was subjected to the surface treatments (blast treatments 1 to 10 and acid treatment 1) shown in Table 3 below. The surface roughness Sq and surface roughness Sku were measured by the following method. The measurement results are shown in Tables 2 and 3.

[0061] <Method of measuring surface roughness Sq and surface roughness Sku> The surface roughness Sq and surface roughness Sku of the formed resin substrate (resin substrate after surface treatment) were calculated using an electron microscope (Keyence VHX7000) by Opt-SEM measurement in high-resolution depth synthesis mode at a magnification of 1500 times to obtain images of the resin substrate surface, and the analysis software of the same device was used.

[0062] The specific treatments for the blast treatments 1 to 10 and the acid treatment 1 are shown below.

[0063] -Blast processing 1- Each side of the formed resin substrate was blasted using a sandblaster with a 1.5 cm aperture, a media injection pressure of 0.2 MPa, a distance of 1 cm between the sandblaster nozzle and the laminate, and a media injection time of 1 second. The media attached to the treated sample was removed using an air gun at an injection pressure of 0.2 MPa.

[0064] -Blast processing 2- The same treatment as in blast treatment 1 was carried out, except that the injection pressure was changed from 0.2 MPa to 0.3 MPa.

[0065] -Blast processing 3- The same treatment as in blast treatment 1 was carried out, except that the injection pressure was changed from 0.2 MPa to 0.4 MPa.

[0066] -Blast processing 4- The same treatment as in blast treatment 1 was carried out, except that the injection pressure was changed from 0.2 MPa to 0.5 MPa.

[0067] -Blast processing 5- The same treatment as in blast treatment 1 was carried out, except that the injection pressure was changed from 0.2 MPa to 0.6 MPa.

[0068] -Blast processing 6- The same treatment as in blasting treatment 1 was carried out, except that the injection pressure was changed from 0.2 MPa to 1 MPa.

[0069] -Blast Processing 7- Blasting treatment 3 was carried out in the same manner as in blasting treatment 3, except that the distance between the nozzle of the sandblaster and the laminate was changed from 1 cm to 10 cm.

[0070] -Blast processing 8- Blasting treatment 3 was carried out in the same manner as in blasting treatment 3, except that the distance between the nozzle of the sandblaster and the laminate was changed from 1 cm to 20 cm.

[0071] -Blast Processing 9- Blasting treatment 3 was carried out in the same manner as in blasting treatment 3, except that the distance between the nozzle of the sandblaster and the laminate was changed from 1 cm to 30 cm.

[0072] -Blast Processing 10- The same treatment as in blast treatment 1 was carried out, except that the media ejection time was changed from 1 second to 20 seconds.

[0073] -Blast Processing 11- The same treatment as in blasting treatment 1 was carried out, except that the media ejection time was changed from 1 second to 30 seconds.

[0074] -Blast Processing 12- The blasting treatment was carried out in the same manner as in blasting treatment 1, except that the injection pressure was changed from 0.2 MPa to 0.1 MPa.

[0075] -Acid treatment 1- The resin substrate thus formed was immersed in a 200 mL container containing a 2 mol NaOH aqueous solution, ultrasonically cleaned for 15 minutes, and then washed with pure water.Then, it was dried in a thermostatic chamber at 60°C for 20 minutes. Then, 400 g / dm of chromic anhydride (Kanto Chemical Co., Ltd.) 3 , sulfuric acid (Kanto Chemical Co., Ltd.) 400g / dm 3 was added to pure water, immersed in the prepared aqueous chromic acid solution, and stirred with a stirrer at 70°C for 5 minutes. Thereafter, the substrate was washed with pure water and dried in a thermostatic chamber at 60° C. for 20 minutes.

[0076] <Metal plating treatment (hereinafter sometimes referred to as "metal plating treatment 1")> -First process (electroless plating)- The formed resin substrate (surface-treated resin substrate) was immersed in a 200 mL container containing a 2 mol NaOH aqueous solution and subjected to ultrasonic cleaning for 15 minutes, and then washed with pure water. Thereafter, the substrate was dried in a thermostatic bath at 60° C. for 20 minutes, and then immersed in Nickel Boomer CON1 liquid (manufactured by Nippon Kagaku Sangyo Co., Ltd.), stirred with a stirrer at 24° C. for 10 minutes, and then washed with pure water. Thereafter, the substrate was immersed in Nickel Boomer 46 solution (manufactured by Nippon Chemical Industry Co., Ltd.), stirred with a stirrer at 60° C. for 1 minute, and then washed with pure water. Thereafter, the substrate was immersed in Nickel Boomer 8509B-B solution (manufactured by Nippon Kagaku Sangyo Co., Ltd.) and stirred with a stirrer at 60° C. for 30 seconds, and then washed with pure water. Thereafter, the process from the immersion in the Nickel Boomer 46 liquid was repeated twice. Thereafter, electroless nickel plating solution 1 (Nickel Boomer 8509M, manufactured by Nippon Kagaku Sangyo Co., Ltd.) was stirred with a stirrer at 60° C., and then the substrate was washed with pure water and dried in a thermostatic bath at 60° C. for 20 minutes.

[0077] -Second process (electrolytic plating)- The resin substrate that was electrolessly plated in the first step was immersed in a tank containing the electrolytic copper plating solution obtained in the following Preparation Example, and the plating was conducted at a current density of 5 A / dm2 at 24°C using a DC stabilized power supply IPS-3610D (manufactured by ISO-TECH). 2 The copper electroplating treatment was carried out and the copper was washed with pure water. When the layer structure and film thickness of the metal plating were measured, it was found that electroless nickel plating with a film thickness of 1 μm and copper plating with a film thickness of 5 μm were formed on the nickel plating. --Example of preparation of electrolytic copper plating solution-- The electrolytic copper plating solution was prepared by adding 200 g / L of copper sulfate pentahydrate (Kanto Chemical Co., Ltd.), 0.15 g / L of copper chloride dihydrate (Kanto Chemical Co., Ltd.), and 50 g / L of sulfuric acid (Kanto Chemical Co., Ltd.) to pure water and adjusting the pH to 0.5.

[0078] The adhesion between the resin substrate and the metal plating (hereinafter sometimes referred to as "adhesion") was evaluated in Examples 1 to 10 and Comparative Examples 1 to 5. The evaluation results are shown in Tables 2 and 3.

[0079] (Adhesion) Using a cutter guide, 11 cuts were made vertically and horizontally at 1 mm intervals on the resin-metal composite to create 100 grids. Nichiban Cellotape (registered trademark) No. 405 was firmly pressed onto the grids and peeled off in one go to check the frequency of exposed substrate. The adhesion between the resin substrate and the metal plating was evaluated based on the following criteria. [Evaluation Criteria] A: Peeling is less than 20% of the total B: Peeling is 20% or more but less than 50% of the total C: Peeling is more than 50%

[0080] [Table 2]

[0081] [Table 3]

[0082] (Examples 11 to 27 and Comparative Examples 6 to 11) <Preparation of Resin Substrate> A resin substrate was formed using the inks shown in Tables 4 to 6 below in the same manner as in Example 1. The surface roughness Sq and the surface roughness Sku were measured in the same manner as in Example 1. The measurement results are shown in Tables 4 to 6.

[0083] <Metal plating treatment> The resin substrate thus formed was subjected to a metal plating treatment in the same manner as in Example 1 to form a resin-metal composite.

[0084] In Examples 11 to 27 and Comparative Examples 6 to 11, the adhesion between the resin substrate and the metal plating was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 4 to 6.

[0085] [Table 4]

[0086] [Table 5]

[0087] [Table 6]

[0088] (Examples 28 to 56 and Comparative Examples 12 to 14) <Preparation of Resin Substrate> Resin substrates were formed in the same manner as in Example 1 using the inks shown in Tables 7 to 10 below.

[0089] <Surface treatment> The surface of the formed resin substrate was subjected to the surface treatment shown in Tables 7 to 10. The surface roughness Sq and the surface roughness Sku were measured in the same manner as in Example 1. The measurement results are shown in Tables 7 to 10.

[0090] <Metal plating treatment> The formed resin substrate (or the surface-treated resin substrate, if a surface treatment was performed) was subjected to metal plating treatments (metal plating treatments 1 to 16) shown in Tables 7 to 10. Specific treatments for metal plating treatments 2 to 16 are shown below.

[0091] -Metal plating process 2- Metal plating was performed in the same manner as in the metal plating process 1, except that the immersion time in the electroless nickel plating solution 1 in the first step was changed to 200 minutes and the second step was not performed. When the layer structure and film thickness of the metal plating were measured, it was found that electroless nickel plating with a film thickness of 10 μm was formed.

[0092] -Metal plating process 3- Metal plating was performed in the same manner as in Metal Plating Process 1, except that the treatment time of the electrolytic copper plating was changed. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating having a film thickness of 1 μm and a copper plating having a film thickness of 20 μm were formed on the electroless nickel plating.

[0093] -Metal plating process 4- Metal plating was performed in the same manner as in Metal Plating Process 1, except that the electrolytic copper plating solution in Metal Plating Process 1 was changed to the electrolytic nickel plating solution obtained in the following Preparation Example, and electrolytic nickel plating was performed according to the following procedure. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating layer with a film thickness of 1 μm and a nickel plating layer with a film thickness of 20 μm were formed on the electroless nickel plating layer. --Example of preparation of electrolytic nickel plating solution-- The electrolytic nickel plating solution was prepared by adding 300 g / L of nickel sulfate hexahydrate (Kanto Chemical Co., Ltd.), 45 g / L of nickel chloride hexahydrate (FUJIFILM Wako Pure Chemical Industries, Ltd.), and 40 mg / L of boric acid to pure water and adjusting the pH to 2.5 to 5. --Electrolytic Nickel Plating-- The resin substrate that was electrolessly plated in the first process was immersed in a tank containing electrolytic nickel plating solution, and a current density of 5 A / dm was applied at 55°C using a DC stabilized power supply IPS-3610D (manufactured by ISO-TECH). 2 The nickel plating was then performed and the resultant was washed with pure water.

[0094] -Metal plating process 5- Metal plating was performed in the same manner as in the metal plating process 1, except that in the second step, electrolytic nickel plating was further performed using an electrolytic nickel plating solution and the treatment time for copper plating was changed. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating with a film thickness of 1 μm, a copper plating with a film thickness of 10 μm was formed on the electroless nickel plating, and a nickel plating with a film thickness of 20 μm was formed on the copper plating.

[0095] -Metal plating process 6- Metal plating was performed in the same manner as in Metal Plating Process 5, except that the copper plating treatment time and the nickel plating treatment time were changed in Metal Plating Process 5. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating with a film thickness of 1 μm, a copper plating with a film thickness of 20 μm was formed on the electroless nickel plating, and a nickel plating with a film thickness of 10 μm was formed on the copper plating.

[0096] -Metal plating process 7- Metal plating was performed in the same manner as in Metal Plating Process 6, except that the nickel plating treatment time was changed. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating layer with a film thickness of 1 μm, a copper plating layer with a film thickness of 20 μm was formed on the electroless nickel plating layer, and a nickel plating layer with a film thickness of 20 μm was formed on the copper plating layer.

[0097] -Metal plating process 8- Metal plating was performed in the same manner as in Metal Plating Process 7, except that the copper plating treatment time was changed. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating layer with a film thickness of 1 μm, a copper plating layer with a film thickness of 30 μm was formed on the electroless nickel plating layer, and a nickel plating layer with a film thickness of 20 μm was formed on the copper plating layer.

[0098] -Metal plating process 9- Metal plating was performed in the same manner as in Metal Plating Process 7, except that the copper plating treatment time was changed in Metal Plating Process 7. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating with a film thickness of 1 μm, a copper plating with a film thickness of 100 μm was formed on the electroless nickel plating, and a nickel plating with a film thickness of 20 μm was formed on the copper plating.

[0099] -Metal plating process 10- Metal plating was performed in the same manner as in Metal Plating Process 5, except that the nickel plating treatment time was changed in Metal Plating Process 5. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating layer with a film thickness of 1 μm, a copper plating layer with a film thickness of 10 μm was formed on the electroless nickel plating layer, and a nickel plating layer with a film thickness of 10 μm was formed on the copper plating layer.

[0100] -Metal plating process 11- Metal plating was performed in the same manner as in Metal Plating Process 8, except that in the second step, electrolytic chrome plating was further performed according to the following procedure using an electrolytic chrome plating solution obtained in the following Preparation Example. When the layer structure and film thickness of the metal plating were measured, it was found that electroless nickel plating with a film thickness of 1 μm, copper plating with a film thickness of 30 μm was formed on the nickel plating, nickel plating with a film thickness of 20 μm was formed on the copper plating, and chrome plating with a film thickness of 0.5 μm was formed on the nickel plating. --Example of preparation of electrolytic chrome plating solution-- The electrolytic chromium plating solution was prepared by adding 250 g / L of chromic anhydride (Kanto Chemical Co., Ltd.) and 2.5 g / L of sulfuric acid (Kanto Chemical Co., Ltd.) to pure water and adjusting the pH to 0.5 to 4. --Electrolytic chrome plating-- The resin substrate was immersed in a tank containing electrolytic chrome plating solution, and the plating was conducted at a temperature of 55°C and a current density of 10 A / dm using a DC stabilized power supply IPS-3610D (manufactured by ISO-TECH). 2 The mixture was then subjected to chrome plating and washed with pure water.

[0101] -Metal plating process 12- Metal plating was performed in the same manner as in Metal Plating Process 8, except that the third step described below was further performed after the second step in Metal Plating Process 8. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating with a film thickness of 1 μm was formed, a copper plating with a film thickness of 30 μm was formed on the nickel plating, a nickel plating with a film thickness of 20 μm was formed on the copper plating, and a nickel plating with a film thickness of 1 μm was formed on the nickel plating. --Third process (electroless plating)-- The resin substrate after the electroless plating in the second step was immersed in a 200 mL container containing a 1 mol NaOH aqueous solution and ultrasonically cleaned for 15 minutes, and then washed with pure water. Thereafter, the substrate was dried in a thermostatic chamber at 60°C for 20 minutes, and then immersed in a Nickel Boomer CON1 liquid and stirred with a stirrer at 24°C for 10 minutes, and then washed with pure water. Thereafter, the specimen was immersed in Nickel Boomer 46 solution and stirred with a stirrer at 60°C for 1 minute, and then washed with pure water. Thereafter, the specimen was immersed in Nickel Boomer 8509B-B liquid, stirred with a stirrer at 60°C for 30 seconds, and then washed with pure water. Thereafter, the process from the immersion in the Nickel Boomer 46 liquid was repeated twice. Electroless nickel plating solution 3 obtained in the following Preparation Example is stirred with a stirrer at 60° C., washed with pure water, and dried in a thermostatic bath at 60° C. for 20 minutes. --Preparation example of electroless nickel plating solution 3-- The electroless nickel plating solution 3 was obtained by adding 16 g / L of nickel sulfate (manufactured by Kanto Chemical Co., Ltd.), 24 g / L of sodium phosphinate (manufactured by Kanto Chemical Co., Ltd.), 16 g / L of sodium succinate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 18 g / L of malic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to pure water and adjusting the pH to 5.6.

[0102] -Metal plating process 13- Metal plating was performed in the same manner as in the metal plating process 2, except that the electroless nickel plating solution 1 in the metal plating process 2 was changed to the electroless nickel plating solution 2 obtained in the following preparation example. When the layer structure and film thickness of the metal plating were measured, it was found that an electroless nickel plating having a film thickness of 10 μm was formed. --Preparation example of electroless nickel plating solution 2-- The electroless nickel plating solution 2 was obtained by adding 30 g / L of nickel sulfate (Kanto Chemical Co., Ltd.), 10 g / L of sodium phosphinate (Kanto Chemical Co., Ltd.), and 10 g / L of sodium acetate (FUJIFILM Wako Pure Chemical Industries, Ltd.) to pure water and adjusting the pH to 4 to 6.

[0103] -Metal plating process 14- Metal plating was performed in the same manner as in Metal Plating Process 8, except that in Metal Plating Process 8, the electroless nickel plating solution 1 was changed to the electroless nickel plating solution 2. When the layer structure and film thickness of the metal plating were measured, it was found that electroless nickel plating with a film thickness of 1 μm, copper plating with a film thickness of 30 μm was formed on the nickel plating, nickel plating with a film thickness of 20 μm was formed on the copper plating, and nickel plating with a film thickness of 1 μm was formed on the nickel plating.

[0104] -Metal plating process 15- Metal plating was performed in the same manner as in the metal plating process 2, except that the electroless nickel plating solution 1 was changed to the electroless copper plating solution obtained in the following Preparation Example. When the layer structure and film thickness of the metal plating were measured, electroless copper plating with a film thickness of 10 μm was formed. --Example of preparation of electroless copper plating solution-- The electroless copper plating solution was prepared by adding 7 g / L of copper sulfate pentahydrate (Kanto Chemical Co., Ltd.), 25 g / L of EDTA (Sigma-Aldrich Co., Ltd.), 6.5 mL / L of 40% formaldehyde (Fujifilm Wako Pure Chemical Industries, Ltd.), and 60 mg / L of sodium cyanide (Fujifilm Wako Pure Chemical Industries, Ltd.) to pure water and adjusting the pH to 12.6.

[0105] -Metal plating process 16- Metal plating was performed in the same manner as in Metal Plating Process 8, except that the electroless nickel plating solution 1 in Metal Plating Process 8 was changed to an electroless copper plating solution. When the layer structure and film thickness of the metal plating were measured, it was found that electroless nickel plating with a film thickness of 1 μm, copper plating with a film thickness of 30 μm was formed on the nickel plating, nickel plating with a film thickness of 20 μm was formed on the copper plating, and nickel plating with a film thickness of 1 μm was formed on the nickel plating.

[0106] In Examples 28 to 56 and Comparative Examples 12 to 14, "three-point bending stress," "adhesion after three-point bending stress test," "corrosion resistance," and "reproducibility" were evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 7 to 10.

[0107] (3-point bending stress) A three-point bending test was performed on the resin-metal composite using an autograph AGS-X (manufactured by Shimadzu Corporation) in accordance with JIS K7171 to measure the three-point bending stress. The three-point bending stress was evaluated based on the measurement results and the following evaluation criteria. The three-point bending stress was calculated from the maximum test force (bending load) using the following calculation formula.

number

[0108] (Adhesion after three-point bending test) After the three-point bending test, the adhesion between the resin substrate and the metal plating of the resin-metal composite was visually observed, and the adhesion after the three-point bending test was evaluated based on the following evaluation criteria. [Evaluation Criteria] A: No change in shape B: The metal plating has peeled off from the resin base material, and the surface is locally rough and wavy. C: The metal plating has completely peeled off from the resin base material, and the surface is rough and wavy.

[0109] (corrosion resistant) By spraying 5% neutral salt water onto the resin-metal composite, the adhesion amount was 20±5mg / cm 2 After leaving the sample to stand for 1 hour at 35° C., the change in shape was visually observed, and the corrosion resistance was evaluated based on the following evaluation criteria. [Evaluation Criteria] A: No change in shape B: Localized discoloration is observed C: Discoloration is observed throughout the sample.

[0110] (Reproducibility) Three cuts were made in the resin-metal composite at 5 mm intervals, lengthwise and crosswise, to create a grid pattern. Cellotape (registered trademark) No. 405 manufactured by Nichiban was firmly pressed onto the grid pattern and the frequency of exposure of the substrate when it was quickly peeled off was confirmed, and the adhesion between the resin substrate and the metal plating was evaluated three times based on the adhesion evaluation criteria below. The reproducibility was evaluated from the results of the three adhesion evaluations, based on the reproducibility evaluation criteria below. [Adhesion evaluation criteria] A: Peeling is less than 20% of the total B: Peeling is 20% or more but less than 50% of the total C: Peeling is more than 50% [Reproducibility evaluation criteria] 3: Three out of three adhesion evaluations were rated "B" or higher 2: Of the three adhesion evaluations, the evaluation result was "B" or higher 2 or more times but less than 3 times 1: Of the three adhesion evaluations, the evaluation result was "B" or higher once or twice but less than twice 0: Of the three adhesion evaluations, 0 were rated "B" or higher

[0111] [Table 7]

[0112] [Table 8]

[0113] [Table 9]

[0114] [Table 10]

[0115] The aspects of the embodiment of the present invention are as follows, for example. <1> A resin-metal composite comprising: a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less; and a metal plating on the resin substrate. <2> The resin base material contains a filler. <1> The resin-metal composite according to claim 1 . <3> The filler is at least one of cellulose nanofiber, glass fiber, and bismaleimide resin. <2> The resin-metal composite according to claim 1 . <4> The average thickness of the metal plating is 20 μm or more. <1> from <3> The resin-metal composite according to any one of claims 1 to 4. <5> The metal plating includes at least one of copper plating and nickel plating. <1> from <4> The resin-metal composite according to any one of claims 1 to 4. <6> The metal plating includes copper plating and nickel plating, and the thickness of the copper plating is at least 1 times the thickness of the nickel plating. <1> from <5> The resin-metal composite according to any one of claims 1 to 4. <7> The resin substrate is not acid-treated or blast-treated. <1> from <6> The resin-metal composite according to any one of claims 1 to 4. <8> A method for producing a resin-metal composite, comprising plating a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less. <9> The plating process includes a base layer forming step of performing electroless plating and a subsequent electrolytic plating layer forming step of performing electrolytic plating. <8> The method for producing a resin-metal composite according to claim 1 . <10> The method further includes a step of forming an electroless plating layer following the step of forming the electroless plating layer, in which the electroless plating layer is formed using an electroless nickel solution containing a phosphorus-nickel compound having a phosphorus content of 5% or more. <9> The method for producing a resin-metal composite according to claim 1 . <11> The method does not include a step of subjecting the resin substrate to an acid treatment or a blast treatment. <8> from <10> 13. The method for producing a resin-metal composite according to claim 12, [Explanation of symbols]

[0116] 10 Resin substrate 20 Metal plating 100 Resin metal composite [Prior art documents] [Patent documents]

[0117] [Patent Document 1] JP 2008-290295 A

Claims

1. A resin-metal composite comprising: a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less; and a metal plating on the resin substrate.

2. The resin-metal composite according to claim 1 , wherein the resin substrate contains a filler.

3. The resin-metal composite according to claim 2 , wherein the filler is at least one of cellulose nanofiber, glass fiber, and bismaleimide resin.

4. The resin-metal composite according to claim 1 , wherein the metal plating has an average film thickness of 20 μm or more.

5. The resin-metal composite according to claim 1 , wherein the metal plating includes at least one of copper plating and nickel plating.

6. The resin-metal composite according to any one of claims 1 to 2, wherein the metal plating includes copper plating and nickel plating, and the thickness of the copper plating is at least one time the thickness of the nickel plating.

7. The resin-metal composite according to claim 1 , wherein the resin substrate has not been subjected to an acid treatment or a blast treatment.

8. A method for producing a resin-metal composite, comprising plating a resin substrate having a surface roughness Sq of 1.5 μm or more and a surface roughness Sku of 4.5 μm or less.

9. The method for producing a resin-metal composite according to claim 8, wherein the plating treatment includes a base layer forming step of performing electroless plating and a subsequent electrolytic plating layer forming step of performing electrolytic plating.

10. The electrolytic plating layer forming step is followed by an electroless plating layer forming step, and the electroless plating layer forming step is performed by using an electroless nickel solution containing a phosphorus-nickel compound having a phosphorus content of 5% or more. The method for producing a resin-metal composite according to claim 9.

11. The method for producing a resin-metal composite according to claim 8 , which does not include a step of subjecting the resin substrate to an acid treatment or a blast treatment.

Citation Information

Patent Citations

  • Method for improving binding force of coating on plastic surface

    CN113564593A

  • Electromagnetic wave shielding film, its manufacturing method and applications

    JP2020510985A

  • Plastic plated product and its manufacturing process

    JP2008290295A